Regularities and trends of formation and development of academic libraries stocks in Siberia (1992-2016) - N. I. Podkorytova; I. G. Lakizo; E. B. Artemyeva (Библиосфера, 2017)
The society development depends directly on the state and evolution of scientific environment, its organizational structures. Academic libraries play the leading role in academic communications, performing functions of informational centers, expanding significantly the field of researchers’ information activity and informational security. Libraries of the Russian Academy of Sciences experienced several stages in their development in 1992-2016, which was defined both by socio-political, socio-economic, legal transformations, and changes in the organizational-administrative model to manage scientific institutions in the country. The development of the library fund of scientific institutions passes several stages: · 1990s - stocks are formed mainly with traditional resources; · early 2000s - stocks structure includes remote access license resources along with traditional carriers; and open access resources - into the servicing system. The authors revealed main trends of stocks development based on results of a brief analysis of the library stocks formation of the Siberian Branch of the Russian Academy of Sciences (SB RAS) in 1992-2016: the united fund created in previous decades breaks up into elements, is atomized, centripetal tendencies are replaced by centrifugal ones, the model of centralization changes, books’ share in the collection of traditional paper editions raises in stocks; it is observed a transition from the acquisition of printed versions of periodicals and special kinds of literature (standards, descriptions of inventions, etc.) to promoting their remote access; SB RAS’ resource base includes licensed electronic resources of remote temporary access and various types of open access scientific information to meet needs of scientists and specialists.